1994
DOI: 10.1162/jocn.1994.6.4.400
|View full text |Cite
|
Sign up to set email alerts
|

Endogenously Generated and Visually Guided Saccades after Lesions of the Human Frontal Eye Fields

Abstract: Nine patients with chronic, unilateral lesions of the dorso-lateral prefrontal cortex including the frontal eye fields (FEF) made saccades toward contralesional and ipsilesional fields. The saccades were either voluntarily directed in response to arrows in the center of a visual display, or were reflexively summoned by a peripheral visual signal. Saccade latencies were compared to those made by seven neurologic control patients with chronic, unilateral lesions of dorsolateral prefrontal cortex sparing the FEF,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
64
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 14 publications
14
64
0
2
Order By: Relevance
“…Work by Rafal, Posner, Friedman, Inhoff and Bernstein (1988) with patients suffering from progressive supranuclear palsy (a disease that affects brain structures involved in saccade control) shows that these patients perform significantly more poorly on tasks that engage exogenous attention than those that require endogenous attention shifts, despite the primary oculomotor deficit being with initiation of voluntary rather than reflexive eyemovements. Similarly, patients with chronic lesions of the FEF have a saccadic deficit but no deficit of endogenous attention (Henik, Rafal, & Rhodes, 1994). More recently, Sereno, Briand, Amador & Szapiel (2006) described a single case with a lesion to the superior colliculus (SC) who showed abnormal reflexive eye-movements and unreliable exogenous attention in a peripheral cueing task (peripheral cueing 22 effects were only observed in two out of the four conditions where they would have been expected), suggesting that exogenous attention is dependent on oculomotor control.…”
Section: Motor Preparation Is Necessary For Spatial Attentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work by Rafal, Posner, Friedman, Inhoff and Bernstein (1988) with patients suffering from progressive supranuclear palsy (a disease that affects brain structures involved in saccade control) shows that these patients perform significantly more poorly on tasks that engage exogenous attention than those that require endogenous attention shifts, despite the primary oculomotor deficit being with initiation of voluntary rather than reflexive eyemovements. Similarly, patients with chronic lesions of the FEF have a saccadic deficit but no deficit of endogenous attention (Henik, Rafal, & Rhodes, 1994). More recently, Sereno, Briand, Amador & Szapiel (2006) described a single case with a lesion to the superior colliculus (SC) who showed abnormal reflexive eye-movements and unreliable exogenous attention in a peripheral cueing task (peripheral cueing 22 effects were only observed in two out of the four conditions where they would have been expected), suggesting that exogenous attention is dependent on oculomotor control.…”
Section: Motor Preparation Is Necessary For Spatial Attentionmentioning
confidence: 99%
“…Consistent with this proposal, studies where human observers prepare but withhold saccades find no evidence of attentional facilitation at the saccade goal (Hunt & Kingstone, 2003;Klein, 1980;Klein & Pontefract, 1994). In addition, patients with lesions to the FEF have problems with saccadic eyemovements but no deficit of covert endogenous attention (Henik et al, 1994). There was evidence from one study that patients who are unable to execute eye-movements experience deficits of endogenous attention (Craighero et al, 2001) but many other studies consistently report preserved endogenous attention but disrupted exogenous attention in ophthalmoplegic patients (Gabay et al, 2010;Rafal et al, 1988;Smith et al, 2004).…”
Section: An Alternative Theoretical Frameworkmentioning
confidence: 99%
“…Furthermore, the FEF is capable of inhibiting location-specific activation within the SC through inhibitory links through the caudate and substantia nigra (e.g., Passingham, 1993). The inhibitory role of the FEF is primarily based on lesion studies, which have shown that FEF lesions result in a deficit in inhibiting reflexive saccades (Guitton, Buchtel & Douglas, 1985;Henik, Rafal & Rhodes, 1994;Rafal et al, 2000). Furthermore, electrical micro-stimulation of the FEF results in suppression of saccades in a variety of tasks (Burman & Bruce, 1997).…”
Section: Exogenous and Endogenous Saccade Controlmentioning
confidence: 99%
“…For this reason, the prosaccade task-set representation does not require many resources and therefore the competition for these resources between the prosaccade task and the secondary task do not result in an impairment of prosaccade performance. It is important to stress that with voluntary prosaccades based on endogenous cueing (e.g., arrows indicating the direction of the eye movement Henik et al, 1994), we expect that a fully elaborated task-set configuration is made and kept active. As a result, interference with these prosaccades would be expected, although the degree of efficiency impairment may be smaller because in this case no inhibition of reflexive saccades is required.…”
Section: Discussionmentioning
confidence: 99%
“…a centrally shown arrow (Henik, Rafal, & Rhodes, 1994). In contrast, the execution of antisaccades requires at least two important subprocesses, namely the suppression of a reflexive saccade towards a visual stimulus and the execution of a saccade in the opposite direction.…”
mentioning
confidence: 99%